2010
DOI: 10.1182/blood-2009-09-245951
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous PEG-asparaginase during remission induction in children and adolescents with newly diagnosed acute lymphoblastic leukemia

Abstract: Over the past several decades, L-asparaginase, an important component of therapy for acute lymphoblastic leukemia (ALL), has typically been administered intramuscularly rather than intravenously in North America because of concerns regarding anaphylaxis. We evaluated the feasibility of giving polyethylene glycosylated (PEG)-asparaginase, the polyethylene glycol conjugate of Escherichia coli L-asparaginase, by intravenous infusion in children with ALL. Between 2005 and 2007, 197 patients (age, 1-17 years) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 10 publications
4
60
0
Order By: Relevance
“…A polyethylene glycol-modified version of L-Asp, pegaspargase (PEG-Asp), was developed in the 1990s with the aim of reducing its immunogenicity (Alfieri et al, 1995). PEG-Asp appears to be safe and effective in patients with acute lymphoblastic leukemia (ALL) (Dinndorf et al, 2007;The Cooperation Group of Phase II Clinical Trial of PEG-Asp, 2008;Silverman et al, 2010); however, the safety and potential efficacy of PEG-Asp in patients with ENKL was not systematically evaluated for future design of relevant clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…A polyethylene glycol-modified version of L-Asp, pegaspargase (PEG-Asp), was developed in the 1990s with the aim of reducing its immunogenicity (Alfieri et al, 1995). PEG-Asp appears to be safe and effective in patients with acute lymphoblastic leukemia (ALL) (Dinndorf et al, 2007;The Cooperation Group of Phase II Clinical Trial of PEG-Asp, 2008;Silverman et al, 2010); however, the safety and potential efficacy of PEG-Asp in patients with ENKL was not systematically evaluated for future design of relevant clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of allergic reactions in patients who were treated with L-asparaginase has been reported to be 30% (38). Studies have reported that pegaspargase therapy had a similar efficacy to L-asparaginase as a treatment in children with acute lymphoblastic leukaemia (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…23 Children treated on the DFCI consortium protocol 05-01 received a single dose of intravenous polyethylene glycol-L-Asp and venous thrombotic events occurred in 4 (2%) of patients, 2 being in the CNS. 24 …”
Section: Effect Of L-asp Preparation On Thrombosismentioning
confidence: 99%